A Simplified Spice Model for IGBT - A. Haddi; A. Maouad; O. Elmazria; A. Hoffmann; J. P. Charles (Active and Passive Electronic Components)
A simplified IGBT (Insulated Gate Bipolar Transistor) SPICE macromodel, based on its equivalent circuit, is proposed. This macromodel is provided to simulate various mechanisms governing the behavior of the IGBT, and it takes into account specific phenomena limiting its SOA (Safe Operating Area), such as forward and reverse biased SOA, as well as latch-up. The validity of this model is confirmed by comparison between simulation and experimental results as well as the data sheets. This comparison is tested for two IGBT devices showing two different powers and switching speeds, and a good agreement is recorded for both IGBT devices.